0282 Elevated levels of Extracellular Vesicle Cytokines are Associated with Poor Sleep Quality in Warfighters with Chronic Mild TBI. (25th May 2022) - Guedes, Vivian; Gottshall, Jackie; Mithani, Sara; Leete, Jackie; Lai, Chen; Gill, Jessica; Kenney, Kimbra; Werner, Kent
Abstract: Introduction: Sleep disorders are common in military populations and frequently occur comorbidly with mild traumatic brain injury (mTBI), resulting in substantial health risks. Although inflammation and cytokine elevations have independently been reported both after traumatic brain injury (mTBI) and in association with sleep dysfunction, the impact of these factors on inflammatory processes in a combined context (i.e. post-mTBI sleep dysfunction) has yet to be explored. Extracellular vesicles (EVs) are a particularly promising source of these cytokines; EVs are lipid bilayer-enclosed particles released by cells to the extracellular environment, constituting a newly discovered form of cell-to-cell communication that may afford improved signal-to-noise ratio and more functionally specific protein biomarkers than free (soluble) sources. To determine whether mTBI and sleep dysfunction may bidirectionally regulate inflammatory processes, the present study examined associations between plasma and EV levels of cytokines and sleep quality in a cohort of warfighters with and without chronic mTBI. Methods: Participants (n=182) were enrolled in the Chronic Effects of Neurotrauma Consortium (CENC) Multicenter Prospective Longitudinal Study/ Long-Term Impact of Military Brain Injury Consortium (LIMBIC). They were divided into control (no TBI history) or mTBI groups (positive history of mTBI). EV and plasma levels of interleukin (IL)-10, IL-6, and tumor necrosis factor-alpha (TNFα) were analyzed using a Simoa HD-1 analyzer. Sleep quality was evaluated using Pittsburgh Sleep Quality Index (PSQI). Results: Within the mTBI group, patients reporting poor sleep quality (PSQI ≥10) had elevated EV levels of IL-10 (ß(SE) = 0.12(0.04), p<0.01) when compared to those reporting good sleep (PSQI<10). Sleep quality was associated with EV levels of IL-10 (ß(SE)=0.11(0.04), p=0.01) and TNFα (ß(SE)=0.07(0.03), p< 0.01) in mTBI patients. Plasma levels of cytokines were not significantly associated with sleep quality. Conclusion: Our findings suggest that EV levels of IL-10 and TNFα, but not their plasma levels, are associated with self-reported sleep quality warfighters with history of mTBI. Our results suggest that EVs are relevant signaling mechanisms in sleep-related inflammatory responses following mTBI. Larger prospective studies are needed to further investigate the links between EV cytokines and sleep quality in participants with mTBI. Support (If Any): This work was supported by grant funding from: Department of Defense, Chronic Effects of Neurotrauma Consortium (CENC) Award W81XWH-13-2-0095 and Department of Veterans Affairs CENC Award I01 CX001135.